Collaborative Painting as a Media for Anti-Bullying Campaign in School Environment - Hikmawaty, Lisna; Bestin, Bakti; Fajar Nugroho, Oktian; Juwita, Silvia Ratna (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2025)
Collaborative painting is an activity where several individuals; students, at school combine 20x20 canvases into one large canvas. The purpose of this research is to analyze the paintings created by students from a psychological perspective; their relationship with the students' emotional and social aspects. The research method uses semiotic analysis, focusing on the relationship between signs, meanings, and social and cultural contexts. Research data were obtained by examining the paintings created by the students. Data analysis is presented descriptively to explain the signs and meanings contained in the paintings. The findings show that collaborative paintings can serve as a bridge to build cooperation and empathy among students. The resulting paintings can be utilized as part of an art intervention for bullying prevention that is oriented towards social values.